2020
DOI: 10.1042/bsr20193515
|View full text |Cite|
|
Sign up to set email alerts
|

The role of DOT1L in the proliferation and prognosis of gastric cancer

Abstract: Background: Disruptor of telomeric silencing-1-like (DOT1L), a methyltransferase of H3K79, was observed to be amplified and overexpressed in certain malignancies. This work was aimed at investigating the differences in DOT1L expression and its regulatory mechanism in gastric cancer (GC) and healthy samples. Methods: Immunohistochemistry was used to detect DOT1L levels in 101 cases of GC and marching adjacent normal tissues. DOT1L was inhibited by small interfering RNA (siRNA) and EPZ5676; a targeting drug. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…These data provide evidence to demonstrate that DOT1L upregulation upon OIS induction occurs in multiple models and cell types and is associated with increased IL1A . Indeed, previous reports have shown that DOT1L suppresses senescence in yeast ( Kozak et al, 2010 ) and plays a protective role in UV-induced melanomagenesis ( Zhu et al, 2018 ), although other studies have shown the opposite ( Barry et al, 2009 ; Jones et al, 2008 ; Kim et al, 2012 ; Nassa et al, 2019 ; Roidl et al, 2016 ; Song et al, 2020 ; Yang et al, 2019 ; Zhang et al, 2014 ), suggesting that DOT1L activity and 1H3K79 methylation are context dependent. The discrepancy between these studies is not clear; it is possible that this is an inherent distinction between model systems.…”
Section: Resultsmentioning
confidence: 99%
“…These data provide evidence to demonstrate that DOT1L upregulation upon OIS induction occurs in multiple models and cell types and is associated with increased IL1A . Indeed, previous reports have shown that DOT1L suppresses senescence in yeast ( Kozak et al, 2010 ) and plays a protective role in UV-induced melanomagenesis ( Zhu et al, 2018 ), although other studies have shown the opposite ( Barry et al, 2009 ; Jones et al, 2008 ; Kim et al, 2012 ; Nassa et al, 2019 ; Roidl et al, 2016 ; Song et al, 2020 ; Yang et al, 2019 ; Zhang et al, 2014 ), suggesting that DOT1L activity and 1H3K79 methylation are context dependent. The discrepancy between these studies is not clear; it is possible that this is an inherent distinction between model systems.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, DOT1, the yeast homolog of DOT1L, suppresses senescence (Kozak et al, 2010), and DOT1L plays a protective role in UV-induced melanomagenesis (Zhu et al, 2018). In contrast, other studies have associated decreased H3K79 methylation and DOT1L expression with loss of proliferation and senescence (Barry et al, 2009;Jones et al, 2008;Kim et al, 2012;Nassa et al, 2019;Roidl et al, 2016;Song et al, 2020;Yang et al, 2019;Zhang et al, 2014). The discrepancy between these studies is not clear.…”
Section: Discussionmentioning
confidence: 98%
“…The mutation of FOS is reportedly associated with poor prognosis in colorectal cancer, 55 and high expression of DOT1L and VEGFA indicates poor prognosis in many cancers, such as lung cancer, gastric cancer, and clear cell renal cell carcinoma. 56–59 These reports imply that mutation of these genes is potentially associated with the prognosis of ESCC as well. However, we failed to detect a correlation between these mutations and the disease-free survival of ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation of FOS is reportedly associated with poor prognosis in colorectal cancer, 55 and high expression of DOT1L and VEGFA indicates poor prognosis in many cancers, such as lung cancer, gastric cancer, and clear cell renal cell carcinoma. [56][57][58][59] These reports imply that mutation of these genes is potentially associated with the Figure 6 The correlation between metastatic lymph node status and the prognosis of ESCC patients. (A) The differential analysis of disease-free survival of patients with and without metastatic lymph nodes.…”
Section: Discussionmentioning
confidence: 99%